Cognitive, metacognitive and motivational perspectives on preflection in self-regulated online learning - Lehmann, T.; Hähnlein, I.; Ifenthaler, Dirk (Elsevier, 2014)
Self-regulated learning is regarded as a critical component of successful online education. Hence, the development of effective online education requires an orchestration of external control and freedom for self-regulation. Prompts are regarded as effective means for promoting such personalised and adaptive learning processes in online education. Within two experimental studies, the effectiveness of preflective and reflective prompts is tested. Additionally, personal characteristics such as motivation and learning preferences are controlled. Results indicate that directed preflective prompts work best for novice learners. Such prompts also activate positive motivation within online learning environments. Still, more research is needed for investigating personalised and adaptive realisation of preflective prompts as well as automated feedback for SRL. © 2013 Elsevier Ltd. All rights reserved.